Risk of tuberculosis reactivation during interleukin‐17 inhibitor therapy for psoriasis: a systematic review. (15th March 2020) - Fowler, E.; Ghamrawi, R.I.; Ghiam, N.; Liao, W.; Wu, J.J.
Abstract: Immunosuppressive therapies, effective in treating inflammatory disorders such as psoriasis, increase the risk of serious infections, such as tuberculosis (TB). For example, tumour necrosis factor (TNF)‐alpha inhibitors significantly increase the risk of TB reactivation in patients with latent TB infection (LTBI), which has led clinicians to routinely test for TB prior to initiation of these medications. This protocol has since extended to other, newer immunomodulatory therapies for psoriasis, such as interleukin (IL)‐17 inhibitors, including secukinumab, ixekizumab and brodalumab. We conducted a systematic review to examine whether there is any evidence that IL‐17 inhibitor therapy for psoriasis increases the risk of TB reactivation. Using PubMed and EMBASE, our literature search resulted in 139 total articles. After manually reviewing each article for the discussion of IL‐17 inhibitors for psoriasis, with data originating from clinical trials, and assessment for incidence of TB reactivation, 23 articles met the full inclusion criteria for our review. Overall, we found no cases of TB reactivation in patients treated with IL‐17 inhibitors for psoriasis. This suggests that IL‐17 inhibitors may be safely used in psoriasis patients with LTBI who receive appropriate LTBI treatment. However, long‐term real‐world studies are warranted to further evaluate this risk.